1971
DOI: 10.1111/j.1432-1033.1971.tb01474.x
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage of Pyrophosphorylethanolamine to Heptose in the Core of Salmonella minnesota Lipopolysaccharides

Abstract: Mild acid hydrolysis of the P+ lipopolysaccharide ol' Salmonella minnesota mRz, a UDPglucose synthetase-less mutant, leads to the formation of 5 degradation products whose structures were studied. Free 2-keto-3-deoxyoctonate (KDO), KDO-7-phosphorylethanolamine, and fraction P-(Hep-Hep-KDO) have been identified previously as degradation products of a Plipopolysaccharide (glycolipid). Fractions P+ (Hep-(Hep-4-phosphate)-KDO) and P P N (Hep-(Hep-4-pyrophosphorylethanolamine)-KDO) occur only i i i the P+ mutant. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The evidence for this is that acid cleavage sufficient to cleave the pyrophosphoryl group internally would also be expected to attack the pyrophosphoryl-sugar linkage to release PPEA, but we did not observe a significant number of rfaP+ core oligosaccharide molecules in which heptose I was completely dephosphorylated. An identical conclusion was reached by Lehmann et al (28), who found that acid treatment of KDO-PPEA released only PPEA. Thus, the question is whether the heterogeneity in the substitution of heptose I is due to an inefficient attachment of PEA to P during synthesis or to enzymatic removal of PEA to generate P during maturation of the LPS.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The evidence for this is that acid cleavage sufficient to cleave the pyrophosphoryl group internally would also be expected to attack the pyrophosphoryl-sugar linkage to release PPEA, but we did not observe a significant number of rfaP+ core oligosaccharide molecules in which heptose I was completely dephosphorylated. An identical conclusion was reached by Lehmann et al (28), who found that acid treatment of KDO-PPEA released only PPEA. Thus, the question is whether the heterogeneity in the substitution of heptose I is due to an inefficient attachment of PEA to P during synthesis or to enzymatic removal of PEA to generate P during maturation of the LPS.…”
Section: Discussionsupporting
confidence: 65%
“…The RcsC protein has a short periplasmic domain, spans the inner membrane, and has a sizable cytoplasmic domain (47) Fig. 8 (10,17,28,32) which showed that the most dramatic LPS structural defect in rfaP mutants was the loss of P or PPE from the heptose I residue. The additional loss of rfaG appears to alter the sensitivity of cells towards novobiocin, as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of Heptose Phosphate It has been shown previously that in the more completed core structures of Ra through Rc mutants some of the heptose residues carry phosphate groups [21]. I n order to evaluate whether D-heptose in the lipopolysaccharide of mutant SL 3147 is likewise phosphorylated, the heptose phosphates were isolated according to the procedure of Slein and Schnell [Wj.…”
Section: Isolation and Identificationmentioning
confidence: 99%